Increased primary breast tumor expression of CD73 is associated with development of bone metastases and is a potential biomarker for adjuvant bisphosphonate use - Petruk, Nataliia; Wood, Steven L.; Gregory, Walter; Lopez-Guajardo, Ana; Oliva, Maria; Mella, Mikko; Sandholm, Jouko; Jukkola, Arja; Brown, Janet E.; Selander, Katri S.S. (Springer Science and Business Media LLC, 2025)
Purpose: Increased CD73 expression has been associated with progression in various cancer types. Results of the AZURE and other trials suggest that, in postmenopausal breast cancer patients, adjuvant bisphosphonates inhibit bone relapses and prolong overall survival. Based on these findings, adjuvant bisphosphonates (typically zoledronic acid) are standard-of-care in postmenopausal patients with high-risk early breast cancer. However, biomarkers are needed for improved patient selection. The aim of this study was to investigate the association of primary tumor CD73 expression with later development of bone metastases.
Methods: To determine whether CD73 levels correlated with tumor parameters (hormone receptor status, tumor stage and grade), patient outcomes (bone metastases and survival) or other patient characteristics (menopausal status, chemotherapy or statin use), we analyzed primary breast tumor CD73 expression immunohistochemically in tumor microarray samples from the AZURE (BIG01/04) trial.
Results: In the AZURE control arm, high CD73 score are significantly prognostic for overall survival (p-value = 0.03, HR = 1.87, 95% CI = 1.06-3.29), disease-free survival (p-value = 0.06, HR = 1.66, 95% CI = 0.982-2.8) and time to first metastasis to bone (p-value = 0.04, HR = 2.23, 95% CI = 1.04-4.81), as compared with low CD73 scores. However, high CD73 score did not display an association with time to non-bone metastasis or first recurrence to a non-skeletal site. In the zoledronate arm, high CD73 score did not have association with patient outcomes, first metastasis to bone, nor with bone recurrence at any time (distant recurrence, including skeletal) or first non-skeletal recurrence. In multivariate testing, CD73 had no significant association with age, ER status, tumor stage, histological grade, menopausal status, chemotherapy or statin use in either arm.
Conclusions: High CD73 expression is associated with development of bone metastases. Zoledronate counteracts this effect. These results suggest that CD73 expression might serve as a biomarker for adjuvant zoledronic acid use.